IDENTIFICATION OF FLOOD RISK FROM TIME FLOODING IN MEDAN BELAWAN - Feby Milanie (International Journal of Management, Economic and Accounting, 2025)
The identification of the flood problem is garbage. Garbage is the cause of the flooding that occurs. Medan Belawan causes water from the Belawan and Deli rivers to enter the area when the sea level is high. The resulting inundation is caused by the land elevation being below the high tide level and river water entering through the drainage channel. The tidal research in Belawan uses descriptive and qualitative methods. The distribution of inundation is analyzed using tidal analysis using the Admiralty method which is input to calculate the distribution of inundation using GIS. The tidal flood risk index is calculated using the threat index and vulnerability index parameters. The results of this study indicate that the disaster risk index in Belawan sub-district is already at high risk with a risk index reaching 0.78.